Analisis Efektivitas dan Strategi Pengembangan Sistem Evaluasi Kinerja Karyawan sebagai Instrumen Strategis untuk Peningkatan Produktivitas SDM di Bank Indonesia Kalimantan Tengah - Delima, Nor; Zakky Zamrudi; Syahrial Shaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
ObjectiveThis study aims to analyze the effectiveness of the employee evaluation system as a strategic instrument in enhancing Human Resource (HR) productivity at Bank Indonesia, Central Kalimantan (BI Kalteng), and to formulate necessary improvement strategies.Method: This descriptive-evaluative research employed a qualitative approach. Primary data was collected through in-depth interviews with the Head of the HR Division, Unit Managers, and executing Employees, utilizing a purposive sampling technique. Data analysis used an interactive model (data reduction, data display, and conclusion drawing) supported by source triangulation.Findings and Discussion: The findings indicate that the performance evaluation system at BI Kalteng has significantly succeeded as a strategic instrument. This success is confirmed by three factors: Strategic Alignment through the implementation of Management by Objectives (MBO), which directs employee energy towards organizational goals; Increased Performance Focus due to the clarity of work objectives and proactive coaching practices; and a Motivational Mechanism that utilizes evaluation results to close competency gaps and design development programs. This success validates the relevance of Strategic Human Resource Management (SHRM) in the context of a regional central bank.Conclusion and Recommendation: Although successful, the system faces operational constraints (limited managerial time for quality feedback) and objectivity challenges. Therefore, the improvement strategy must shift towards a Developmental Performance Management model. Crucial strategies include: Transition to Continuous Coaching, Enhancing Objectivity through Limited Multisource Feedback, and Explicit Integration of evaluation results with Career Paths and Mandatory Individual Development Plans (IDP). These improvements will make the evaluation system a more potent and sustainable accelerator of HR output.